The Effectiveness of Entrepreneurship Curriculum Imple-mentation in Senior High School (SMA) in Buliding Students’ Entrepreneurial Interest and Attitude: Systematic Literature Review (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The persistent issue of high youth unemployment among Senior High School (SHS) graduates necessitates cultivating an entrepreneurial mindset through formal education, making Entrepreneurship Education (EE) a national strategic imperative. This Systematic Literature Review (SLR) critically analyzed 15 empirical articles, selected via the strict PRISMA protocol, to evaluate the effectiveness of diverse EE curriculum models in enhancing students' Entrepreneurial Interest (Intention) and Attitude. The key finding is that EE implementation is substantially effective only when executed through active, experience-based pedagogical models such as Experiential Learning, Project-Based Learning (PjBL), and the Teaching Factory which are superior in fostering practical competency and significantly boosting Entrepreneurial Self-Efficacy and positive Attitude, consistent with the Theory of Planned Behavior. Successful implementation also critically depends on robust operational factors, including structured curriculum management (e.g., PDCA cycle) and the availability of competent teachers. In conclusion, the findings provide a strong evidence-based framework, recommending that policymakers prioritize experiential models and integrate modern elements like Digital Literacy and Non-cognitive Skills to produce SHS graduates with genuine entrepreneurial readiness.